Biomechanical Analysis of a Novel Acetabulum Reconstruction Technique with Acetabulum Reconstruction Cage and Threaded Rods after Type II Pelvic Resections - Singh, V.A.; Elbahri, H.; Shanmugam, R. (Hindawi Publishing Corporation, 2016)
Background. Periacetabular resections with reconstruction has high rates of complications due to the complexity of the reconstruction. We have improvised a novel technique of reconstruction for type II and type II + III pelvic resections with the use of a commercially available acetabulum reconstruction cage (gap II, Stryker) and threaded rods. Objectives. The aim of our study is to determine the biomechanical strength of our reconstruction compared to the traditional cemented total hip replacement (THR) designs in normal acetabulum and establish its mode of failure. Methods. Five sets of hemipelvises were biomechanically tested (Instron® 3848, MA, USA). These constructs were subjected to cyclic loading and load to failure. Results. The reconstructed acetabulum was stiffer and required a higher load to failure compared to the intact pelvis with a standard THR. The mean stiffness of the reconstructed pelvis was  Nmm−1 compared to the intact pelvis, which was  Nmm−1 ( value = 0.01). The mean load to failure for the standard acetabular cup construct was  N while that of the reconstructed pelvis with the acetabulum cage and threaded rods was  N. Conclusion. Reconstruction of the pelvis with an acetabular reconstruction cage and threaded rods is a biomechanical viable option.